Factors Affecting Competitiveness of Vietnamese Online Sales Websites in Integrating Tpp: A Study in Vietnam - Phi Hoang, Tran; Quoc Trong, Bui; Thai Bi?nh, Nguyen; Kim Quy, Huynh (British Journal of Marketing Studies, 2016)
This study is to analyze the factors affecting competitiveness of Vietnamese online sales websites in integrating TPP (Trans - Pacific Partnership). Qualitative and quantitative research methods were used to carry on 800 online customers in Ho Chi Minh City, Danang City and Hanoi City. The study results show that the competition volume of Vietnamese online websites affected by 05 factors as follows: (1) The level of competition, Suppliers, The risk of substitution, Buyer Power, Entry Barrier. Based on the research results, measures are proposed to improve competitiveness for Vietnamese online sales websites in the future. After Analyzing the data, the main objectives of this study were to: First, identify the factors affecting competitiveness of Vietnamese online sales website; Second, determine the priority order of the impact factors affecting competitiveness of Vietnamese online sales websites; Third, propose solutions to enhance competitiveness of Vietnamese online sales websites in integrating TPP.